Pengaruh Harga dan Pelayanan terhadap Kepuasan Mahasiswa pada Politeknik LP3I Jakarta - Nita Ariska (JURNAL LENTERA BISNIS, 2019)
This study aimed to find out how much price influences student of LP3I Polytechnic Jakarta Kramat Campus satisfaction, how much service influences' student of LP3I Polytechnic Jakarta Kramat Campus satisfaction and know how much the price and service influence student of LP3I Polytechnic Jakarta Kramat Campus satisfaction. This study uses a correlation method to see how much influence the independent variables and dependent variables influence. The research polls are level 2 students in the Administration Business Study Program, Computer Informatics, Informatics Engineering, Accounting Computerization, Office Administration of LP3I Polytechnic Jakarta (100 people). Each respondent is given 80 questions using a Likert scale. Based on the results of data management shows that the influence of prices partially has a significant effect on Student satisfaction. This shows that prices influence the satisfaction of LP3I Polytechnic students in Jakarta. Price levels, discount and payment methods affect student satisfaction. The effect of prices partially has a significant effect on student satisfaction. While the effect of service simultaneously has a significant and positive effect on student satisfaction. This shows that together prices and will affect student satisfaction at LP3i Polytechnic Campus Kramat. Where if prices and services are in accordance with student expectations, students will get satisfaction and vice versa.Key Word : price, service, satisfication